Religious tourism and pilgrimage festivals management: an international perspective - Raj, R.; Morpeth, N. D.; Morpeth, N. D.; Raj, R. (Wallingford :CABI, 2007)
Describing practical applications, models and case studies, this book provides an insight into the management of religious tourism, covering both ancient sacred sites and emerging destinations. It examines the relationships between religion and tourism and explores the pressures on sacred spaces to become commercialized and "festivalized" arenas, while still maintaining their religious and spiritual integrity. This book will be of interest to students and researchers in tourism and event management, and will also serve as a practical handbook for practitioners in the industry. The book has 17 chapters and a subject index.
Keywords: EE119 - Leisure, Recreation and Tourism Economics, (New March 2000); UU485 - Social Psychology and Social Anthropology, (New March 2000); UU700 - Tourism and Travel